1992
DOI: 10.3406/rea.1992.4495
|View full text |Cite
|
Sign up to set email alerts
|

L'habitat grec et les fouilles de Thasos

Abstract: La fouille du quartier situé derrière la Porte du Silène, à Thasos, a fourni à Y. Grandjean le point de départ d'une monographie d'archéologie et d'histoire urbaine : l'étude minutieuse de ces maisons, qui ne cessent de se transformer entre 500 et 250 av. J.-C, complétée par les données éparses fournies par les fouilles depuis 1911, révèle les procédés de construction de l'habitat thasien et suggère les modalités d'un urbanisme local apparemment peu influencé par l'abstraction hippodamienne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Such super star clusters are observed in a growing number of starburst systems and may constitute an important mode of star formation in starbursts (e.g. Holtzmann et al 1992;O'Connell, Gallagher, & Hunter 1994;Whitmore & Schweizer 1995;Maoz et al 1996;Tacconi-Garman, Sternberg, & Eckart 1996).…”
Section: A2 Properties and Distribution Of The Ionizing Stellar Clustersmentioning
confidence: 99%
“…Such super star clusters are observed in a growing number of starburst systems and may constitute an important mode of star formation in starbursts (e.g. Holtzmann et al 1992;O'Connell, Gallagher, & Hunter 1994;Whitmore & Schweizer 1995;Maoz et al 1996;Tacconi-Garman, Sternberg, & Eckart 1996).…”
Section: A2 Properties and Distribution Of The Ionizing Stellar Clustersmentioning
confidence: 99%
“…While super star clusters have not yet been seen in the Milky Way or in M31, they have been discovered in large numbers in several environments: in starbursting gas-rich dwarf irregular galaxies (Melnick et al 1985;O'Connell et al 1994;Ho & Filippenko 1996a, 1996bGelatt et al 2001;Billett et al 2002;Vanzi 2003); in more massive starburst galaxies (Holtzmann et al 1992;Whitmore et al 1993;Meurer et al 1995;Whitmore & Schweizer 1995;Zepf et al 1999;Tremonti et al 2001;Lipscy & Plavchan 2004;Turner & Beck 2004;McCrady et al 2005;Melo et al 2005), many of which show signs of recent mergers or interactions; and in the compact group Stephan's Quintet . In some of these galaxies, such as M82, NGC 4038/4039, and NGC 1275, super star clusters incorporate a significant fraction of the starburst (Lipscy & Plavchan 2004;McCrady et al 2005) and are preferentially found in the inner regions of the galaxy (Whitmore & Schweizer 1995;Meurer et al 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Two of the many interesting phenomena discovered by the satellite observatories have been the starburst galaxies and the super star clusters, first identified as important classes by the IRAS and the Hubble Space Telescope (HST) satellites (Soifer et al 1987;Holtzmann et al 1992). The starburst galaxies are characterized by extremely rapid star formation in regions with gas densities up to 20 times higher than the typical densities of normal spiral galaxies (Sanders & Mirabel 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of SSC masses based on population synthesis models indicate a range from below 10 4 up to a few 10 6 M ⊙ Melo et al 2005). The similarity in size and mass of the SSCs and globular clusters have prompted the further suggestion that the SSCs might be present-day analogs of young globular clusters (Holtzmann et al 1992). Previously thought to form strictly in an earlier epoch of galaxy evolution, globular clusters may in fact be forming in the current epoch in starburst environments (Ashman & Zepf 2001).…”
Section: Introductionmentioning
confidence: 99%